Biodiversity litigation - Futhazar, Guillaume; Maljean-Dubois, Sandrine; Razzaque, Jona (Oxford : Oxford University Press, 2022)
Biodiversity is in accelerated decline and urgent action is needed. In 2020, the Strategic Plan for Biodiversity ended, and none of its Aichi Targets were met. Despite the legally disappointing situation on a global level, the role of national courts in adjudicating climate change litigation is showing potential for effective mitigation and adaptation, and judges have become key actors in linking internationally agreed goals with tangible national commitments to mitigate climate change. Can this pursuit of globally agreed goals at a local level be transposed and lead a similar trend for biodiversity governance? This edited collection gives readers an overview of the shape and reach of biodiversity litigation, drawing on specific case studies from countries such as Brazil, China, India and Canada.
This edition also issued in print: 2023.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on December 19, 2022).
Keywords: Biodiversity conservation -- Law and legislation; Biodiversity -- Law and legislation; Actions and defenses; Law; Laws of specific jurisdictions & specific areas of law